DOLOMITES, THEIR FORMATION CONDITIONS AND FEATURES OF TERRITORIAL DISTRIBUTION IN WESTERN UZBEKISTAN - D.Kh, Asabaev; F.A, Badalov; A.A, Normurodov (ANTIS PUBLISHER, 2024)
General Background: Dolomites in Western Uzbekistan serve as vital mineral raw materials across industries like chemical, construction, glass, and metallurgy, with ferrous metallurgy being the largest consumer due to their application as refractory materials. Specific Background: Historically, magnesite dominated this role; however, its depletion and increasing global costs have shifted attention to dolomites as an alternative. Over 60 dolomite deposits in Uzbekistan, particularly those with high MgO content such as Shushaktau and Muruntau, have been identified, offering favorable mining and geological conditions. Knowledge Gap: Despite their potential, these deposits lack industrial recognition due to insufficient technological validation, limiting their widespread use in refractory production. Aims: This study aims to evaluate the geological, chemical, and technological properties of Uzbekistan's dolomite deposits and explore their industrial feasibility. Results: Results show that these deposits possess high chemical purity, horizontal distribution, and minimal tectonic disturbances, making them suitable for producing refractory bricks, metallurgical powder, and fluxes. Replacing imported magnesite with local dolomites could significantly reduce costs and enhance economic viability. Novelty: However, challenges include the absence of semi-industrial testing and limited mining infrastructure. Implications: Future research should focus on comprehensive industrial testing, advanced processing technologies, and market feasibility studies to realize the potential of dolomites as a cost-effective alternative to magnesite, promoting industrial growth and reducing reliance on imports.